1997
DOI: 10.1111/j.1399-302x.1997.tb00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of an oral treponeme isolated from human subgingival plaque

Abstract: We examined the genetic characteristics of a human oral treponeme isolated from subgingival plaque of a patient with periodontal disease that could not be assigned to any of the previously described oral Treponema species. The guanine-plus-cytosine content of its DNA was 51 mole%. The levels of DNA-DNA relatedness of the organism to other Treponema species, including Treponema denticola, Treponema vincentii, Treponema socranskii, Treponema pallidum and Treponema phagedenis, were less than 30%. This study clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…However, it is suggested that DNA–DNA homology still be used to confirm the designation and evaluation of new species, particularly closely related ones (8). Results obtained in this comparative study of 16S rDNA sequences, together with findings on DNA–DNA homology levels in these Treponema species (6), support the conclusion that T. medium represents a phylogenetic lineage distinct from those of all treponemal species established previously.…”
Section: The Characteristics Of Human Oral Treponema Speciessupporting
confidence: 86%
See 1 more Smart Citation
“…However, it is suggested that DNA–DNA homology still be used to confirm the designation and evaluation of new species, particularly closely related ones (8). Results obtained in this comparative study of 16S rDNA sequences, together with findings on DNA–DNA homology levels in these Treponema species (6), support the conclusion that T. medium represents a phylogenetic lineage distinct from those of all treponemal species established previously.…”
Section: The Characteristics Of Human Oral Treponema Speciessupporting
confidence: 86%
“…Our present data completely agree with this conclusion (16). However, the level of DNA–DNA homology between T. medium and T. vincentii has been reported to be 28% (6), suggesting separate species designation. T. medium also showed high sequence similarities to T. denticola (88.4%) and T. phagedenis (88.2%) in this study.…”
Section: The Characteristics Of Human Oral Treponema Speciesmentioning
confidence: 99%
“…Bacterial DNA was extracted using InstaGene Matrix (Bio‐Rad, Hercules, CA) according to the manufacturer's instructions. The DNA concentration was determined at 260 nm (A 260 ), and the purity was estimated by measuring the ratio A 260 /A 280 (10, 20). High performance liquid chromatography (HPLC) was used to determine the G+C content (11, 14, 15, 19, 20).…”
Section: Methodsmentioning
confidence: 99%
“…A DNA preparation (1 mg/ml distilled water) was denatured at 100°C for 5 min. After rapid cooling in an ice bath, the denatured DNA was decomposed with 0.05 U nuclease P1 (Yamasa Shoyu Co., Chiba, Japan) in 40 m m sodium acetate buffer containing 0.2 m m ZnCl 2 at 50°C for 1 h. The hydrolysates and a standard solution of deoxyribonucleotide monophosphates (dAMP, dCMP, dGMP and dTMP) were each subjected to HPLC (L‐6200, Hitachi, Japan) with a 3013‐N column (4 × 150 mm), eluted with a mobile phase containing 30 m m KCl, 10 m m KH 2 PO 4 and 10% CH 3 CN (pH 3.5), and detected with a Hitachi L‐4200 apparatus at 267 nm (20).…”
Section: Methodsmentioning
confidence: 99%
“…These reports support the concept of a close association between the oral treponemes and human periodontal diseases. On the other hand, Nakazawa et al (57) reported that the treponeme species in periodontal pockets could be completely distinct from the known oral Treponema species and the marked genetic heterogeneity among human oral Treponema species. Since few prevalence studies of the specific species of oral Treponema have been reported, the accumulation of more epidemiological data is required in order to clarify this confusion.…”
Section: Oral Treponema and Diseasementioning
confidence: 99%